Amylin Selectively Signals Onto POMC Neurons in the Arcuate Nucleus of the Hypothalamus - Lutz, Thomas A. (Diabetes, 2018)
Amylin phosphorylates ERK (p-ERK) in the area postrema to reduce eating and synergizes with leptin to phosphorylate STAT3 in the arcuate (ARC) and ventromedial (VMN) hypothalamic nuclei to reduce food intake and body weight. The current studies assessed potential amylin and amylin-leptin ARC/VMN interactions on ERK signaling and their roles in postnatal hypothalamic pathway development. In amylin knockout mice, the density of agouti-related protein (AgRP)-immunoreactive (IR) fibers in the hypothalamic paraventricular nucleus (PVN) was increased, while the density of α-melanocyte–stimulating hormone (αMSH) fibers was decreased. In mice deficient of the amylin receptor components RAMP1/3, both AgRP and αMSH-IR fiber densities were decreased, while only αMSH-IR fiber density was decreased in rats injected neonatally in the ARC/VMN with an adeno-associated virus short hairpin RNA against the amylin core receptor. Amylin induced p-ERK in ARC neurons, 60% of which was present in POMC-expressing neurons, with none in NPY neurons. An amylin-leptin interaction was shown by an additive effect on ARC ERK signaling in neonatal rats and a 44% decrease in amylin-induced p-ERK in the ARC of leptin receptor–deficient and of ob/ob mice. Together, these results suggest that amylin directly acts, through a p-ERK–mediated process, on POMC neurons to enhance ARC-PVN αMSH pathway development.